The solar component in the context of the inhabited areas microclimate regulation - Koziatnyk, Iryna (KNUCA, 2015)
Summer overheated modern city deteriorates living conditions in it. For this purpose, the climate formation is considered in three adjacent spatial levels: macroclimate of geographical area; mesoclimate of a certain location (southern slope of the mountain, river valley, the sea coast); microclimate of two-meter surface layer (at the level of the human body). These levels of different spatial scale have similar mechanisms of climate formation. The radiation temperature and wind conditions of the area are the main causes of the overheating. The specified information proposes to research the solar radiation and the surfaces to accumulate it. The urban landscape is predominated over by the surface, which significantly accumulate heat. Hence the surface layer of air in the city receives three times more heat than in the natural environment. Thus, microclimate is formed in the streets, squares, in a housing estate and city parks under the natural and city planning factors. The found that for balancing and softening of microclimate conditions for living and of effective impact on the heat, humidity and aeration regime of the modern city, it is desirable to achieve a ratio of 1:1 between its planting and artificial surfaces.
СОЛНЕЧНАЯ СОСТАВЛЯЮЩАЯ В КОНТЕКСТЕ РЕГУЛИРОВАНИЯ МИКРОКЛИМАТА ЖИЛЫХ ТЕРРИТОРИЙ
Keywords: climate; insolation; residential area; architectural and planning regulations; environmental barrierless environm; климат; инсоляция; жилая территория; архитектурно-планировочное регулирование; экологически безбарьерная среда